Many pathways to literacy young children learning with siblings, grandparents, peers, and communities - Gregory, Eve.; Long, Susi 1952-.; Volk, Dinah (New York RoutledgeFalmer, 2004)
"This unique and visionary text is a compilation of fascinating studies conducted in a variety of cross-cultural settings where children learn language and literacy with siblings, grandparents, peers and community members. Focusing on the knowledge and skills of children often invisible to educators, these illuminating studies highlight how children skilfully draw from their varied cultural and linguistic worlds to make sense of new experiences. The vastly experienced team of contributors provide powerful demonstrations of the generative activity of young children and their mediating partners - family members, peers, and community members - as they syncretise languages, literacies and cultural practices from varied contexts. Through studies grounded in home, school, community school, nursery and church settings, we see how children create for themselves radical forms of teaching and learning in ways that are not typically recognised, understood or valued in schools.This book will be invaluable reading for teachers, teacher educators, researchers and policy-makers who seek to understand the many pathways to literacy and use that knowledge to affect real change in schools."
A sociocultural approach to learning / Eve Gregory, Susi Long, Dinah Volk -- Mediating networks for literacy learning : the role of Puerto Rican siblings / Dinah Volk with Martha de Acosta -- Samia and Sadaqat play school : early bilingual literacy at home / Rose Drury -- ?Right, get your book bags!? : siblings playing school in multiethnic London / Ann Williams -- Buzz Lightyear in the nursery : intergenerational literacy learning in a multi-media age / Clare Kelly -- Storytelling and Latino elders : what can children learn? / Irma Olmedo -- Making a place for peer interaction : Mexican American kindergartners learning language and literacy / Susi Long with Donna Bell and Jim Brown -- Community school pupils re-interpret their knowledge of Chinese and Arabic for primary school peers / Charmian Kenner -- ?How do I read these words?? : bilingual exchange teaching between Cantonese speaking peers / Yuangguang Chen and Eve Gregory -- Friendship literacy : young children as cultural and linguistic experts / Manjula Datta -- Learning to be just : interactions of white working class peers / Rebecca Rogers and Melissa Mosley -- Change and tradition in literacy instruction in a Samoan American community / Alessandro Duranti, Elinor Ochs, and Elia K. Ta?ase -- Multilingual flexibility and literacy learning in an Urdu community school / Leena Helavaara Robertson -- The African American church : a beacon of light on the pathway to literacy for African American children / Gwendolyn McMillon and Patricia A. Edwards -- His eye on the sparrow : teaching and learning in an African American church / Wendy L. Haight and Janet Carter-Black -- Cultural literacy in the world of Pueblo children / Mary Eunice Romero.
Keywords: Language arts (Early childhood) -- Social aspects -- United States -- Cross-cultural studies; Language arts (Early childhood) -- Social aspects -- Great Britain -- Cross-cultural studies; Home and school -- Cross-cultural studies; Community and school -- Cross-cultural studies; Education, Bilingual -- Cross-cultural studies